Associate Professor Dimitris Keridis gives his inaugural lecture in the ASEAN Auditorium. Photo 016 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Associate Professor Dimitris Keridis gives his inaugural lecture in the ASEAN Auditorium.